2020
DOI: 10.1080/16878507.2020.1739801
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of elemental composition of Granite Gneiss collected from Neelum Valley using calibration free laser-induced breakdown and energy-dispersive X-ray spectroscopy

Abstract: Calibrationfree laser-induced breakdown spectroscopy (CF-LIBS) has been employed for elemental analysis of Granite Gneiss, rock sample, collected from Neelum Valley of Azad Jammu & Kashmir, Pakistan. The sample was irradiated with focused laser beam from Q-switched Neodymium Yttrium Aluminum Garnet laser, having 532 nm wavelength and pulse width of 5 ns, and the emission spectrum was recorded with a spectrometer. Overall, ten elements viz. Si, Al, K, Fe, Sr, Ca, Mg, Na, Li, and H were identified by inspecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…It is evident from Table 5 that the percentage error between the measurements of CF-LIBS and XRF techniques range from almost 8% to 18% for major elements (Ti, W, Fe), whereas for minor and trace elements, relative error increases from 17% to 88%. These results are consistent with many previous studies suggesting that CF-LIBS performs almost equivalently well for quantifying major elements in a multi-elemental material, but its efficiency reduces for minor and trace element quantification [ 25 , 26 , 27 , 28 , 29 , 30 ]. However, the advantage of LIBS over XRF is the detection of lighter elements in multi-elemental complex materials.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It is evident from Table 5 that the percentage error between the measurements of CF-LIBS and XRF techniques range from almost 8% to 18% for major elements (Ti, W, Fe), whereas for minor and trace elements, relative error increases from 17% to 88%. These results are consistent with many previous studies suggesting that CF-LIBS performs almost equivalently well for quantifying major elements in a multi-elemental material, but its efficiency reduces for minor and trace element quantification [ 25 , 26 , 27 , 28 , 29 , 30 ]. However, the advantage of LIBS over XRF is the detection of lighter elements in multi-elemental complex materials.…”
Section: Discussionsupporting
confidence: 92%
“…Being free from the matrix effect, CF-LIBS methodology emerges as an effective alternative and gives reasonable and good quantitative results for geological materials of unknown composition. In previous studies, quantitative results obtained with CF-LIBS showed a reasonable agreement with standard analytical techniques [ 26 , 27 , 28 , 29 , 30 ]. There is no need for reference samples and drawing the calibration curves for each element present in the target sample.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In this scenario, the CF-LIBS method appears to be a suitable and effective alternative to the calibration method. In some previous studies, the CF-LIBS method was utilized for measurement of elemental composition of geological samples such as limestone, granite, malachite, and nephrite, and results were compared with standard techniques such as energy dispersive X-ray spectroscopy (EDX), X-ray fluorescence (XRF), and laser ablation-time of flight-mass spectrometer (LA-TOF-MS) [24][25][26]44,45]. In all of these studies, quantitative results obtained with CF-LIBS showed reasonable agreement with the standard analytical techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Harmon et al found out that the dispersion of CNT's in polymer (Poly Methyl Methacrylate) may lessen the degradation of properties with gamma irradiation and concluded that the SWNTs can dissipate the energy by ionizing radiations. Improvement in radiation resistance can also be achieved by incorporating the aromatic compounds into a polymer, either within the structure or as an additive (Abbasi et al, 2020;Hales et al, 2015;Khan et al, 2018;Phillpot et al, 2018;Zhu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%